Acquired esophageal stricture in the dog: a case report - M. Vlasin; R. Husnik; T. Fichtel; L. Rauserova (Veterinární Medicína, 2004)
Complicated case, which after several surgical interventions ended up with an acquired esophageal stricture is presented. The possibility of reflux esophagitis should be kept in mind during postoperative period, especially in primarily troubled patients. An early management of reflux esophagitis could prevent such a condition successfully and help taking full control of a patient after surgery. This report describes etiology of the problem, follows its dynamics, as well as evaluates treatment options suggested in textbook against options available and those finally applied after consulting the owner. Authors try to point out cardial incompetence as one of the most important etiological factors. Despite some early remissions, authors finally succeeded to extend the diameter in the site of the stricture from 5 mm to over 15 mm within seven sessions performed in the period of six months, improving functional outcome.